2022
DOI: 10.1186/s12955-022-02013-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the 12-item WHODAS applied through phone survey: an experience in PERSIAN Traffic Cohort

Abstract: Background Due to limited capability to function in post-injury daily life injury, survivors need to be reliably assessed without need to commute more than necessary. The key action is to determine the level of functioning difficulties. Having the opportunity of conducting a national post-crash traffic safety and health cohort study, we aimed to translate into Persian and assess the psychometric properties of the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…The analysis found that the WHODAS 2.0 test-retest reliability was good (ICC = 0.78), indicating the instrument's ability to produce reproducible results when used repeatedly over a short period of time. This finding appears to be in line with earlier studies, which found the test-retest reliability for the WHODAS 2.0 was in the good range, with ICC of 0.70 or higher in patients with anxiety and stress (ICC = 0.83) [4] and Persian traffic cohort sample (ICC = 0.97) [54]. We also found that the WHODAS 2.0 agreement between self-administered and interviewer-administered modes was good (ICC = 0.89), indicating that functioning and disability ratings by patients and interviewers were generally consistent and therefore considered reliable.…”
Section: Plos Onesupporting
confidence: 92%
“…The analysis found that the WHODAS 2.0 test-retest reliability was good (ICC = 0.78), indicating the instrument's ability to produce reproducible results when used repeatedly over a short period of time. This finding appears to be in line with earlier studies, which found the test-retest reliability for the WHODAS 2.0 was in the good range, with ICC of 0.70 or higher in patients with anxiety and stress (ICC = 0.83) [4] and Persian traffic cohort sample (ICC = 0.97) [54]. We also found that the WHODAS 2.0 agreement between self-administered and interviewer-administered modes was good (ICC = 0.89), indicating that functioning and disability ratings by patients and interviewers were generally consistent and therefore considered reliable.…”
Section: Plos Onesupporting
confidence: 92%
“…In Brazilians with Chagas disease, WHODAS 2.0 showed 3 factors with adequate global internal consistency (Alpha = 0.87) [ 16 ]. The Persian version of WHODAS 2.0 included post-injury daily life injury people and presented 4 factors with excellent total internal consistency (Alpha = 0.92) [ 17 ]. Six factors were reported in the WHODAS 2.0 versions in road traffic trauma victims in Ethiopia [ 18 ] and in children and adolescents with chronic physical illness in Canada [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported different factor structures (e.g., one-factor [ 14 , 15 ], 3-factor [ 16 ], 4-factor [ 17 ], and 6-factor [ 18 , 19 ]) for the 12-item WHODAS 2.0 in varied populations and health conditions that include men and women [ 14 – 19 ]. Thus, it was necessary to assess the structural validity of this WHODAS 2.0 version in a sample of women with dysmenorrhea by exploratory factor analysis and confirmatory factor analysis.…”
Section: Methodsmentioning
confidence: 99%